The Preferences of the Lekuk 50 Tumbi Community in Utilizing Cultural Key Species as Tourism Products - Eliza Sutri Utami; Yoni Elviandri (West Science Social and Humanities Studies, 2026)
Key Cultural Species (CSCs) are an important part of the traditional ecological knowledge of indigenous communities, possessing cultural, ecological, and economic value through the development of local wisdom-based tourism. This study aims to analyze the preferences of the Lekuk 50 Tumbi indigenous community, Kerinci Regency, regarding the use of CSCs as a tourism product. The study employed a mixed methods approach with an exploratory design. Data collection was conducted through structured interviews using a Likert-scale questionnaire, in-depth interviews, and field species identification. Respondents were selected using a purposive sampling technique followed by snowball sampling. The results showed that 82.2% of respondents had not yet been involved in the use of CSCs as a tourism product, although 96.7% expressed interest in being involved in its development in the future. The pitcher plant (Nepenthes ampullaria Jack) was the most popular plant species to be developed as a tourism product (56.7%), while the semah fish (Tor douronensis) was the most frequently chosen animal species (68.9%). The most popular form of involvement was the development of souvenirs in the form of processed food products (45.6%), especially by female respondents. Gender, age, and marital status influence the preferred form of community involvement. These findings indicate that communities are highly prepared and interested in participating in Key Cultural Species-based tourism development. Therefore, developing tourism products that integrate conservation, cultural values, and community empowerment has the potential to be an effective strategy for supporting biodiversity conservation while improving the well-being of indigenous communities.